Abdominopelvic Tuberculosis Secondary to a Nontuberculous Mycobacterium in an Immunocompetent Patient. (13th November 2017) - Ng, Beng Kwang; Yakob, Kembang Aziah; Ng, Wendy Yin Ling; Lim, Pei Shan; Abd Rahman, Rahana; Abdul Karim, Abdul Kadir; Zainuddin, Ani Amelia; Mahdy, Zaleha Abdullah
Abstract : Tuberculosis (TB) remained as one of the top 10 causes of death worldwide despite an overall decline in its incidence rate globally. Extrapulmonary TB is uncommon and only accounts for 10–20% of overall TB disease burden. Abdominopelvic TB is the sixth most common location of extrapulmonary TB. The symptoms and signs are often insidious and nonspecific. Diagnosing abdominopelvic TB can be very challenging at times and poses great difficulties to the clinician. Infection with nontuberculous Mycobacterium (NTM) is even rarer especially in an immunocompetent patient. We report a case of NTM in abdominopelvic TB. A 37-year-old foreign worker, para 3, presented with a one-week history of suprapubic pain associated with fever. An assessment showed presence of a right adnexal mass. She was treated as tuboovarian abscess with intravenous antibiotics. Unfortunately, she did not respond. She underwent exploratory laparotomy. Intraoperatively, features of the mass were suggestive of a right mature cystic teratoma with presence of slough and cheesy materials all over the abdominal cavity as well as presence of ascites. Diagnosis of NTM was confirmed with PCR testing using the peritoneal fluid. This case was a diagnostic dilemma due to the nonspecific clinical presentation. Management of such rare infection was revisited.